Edoxaban-based versus vitamin K antagonist-based antithrombotic regimen after successful coronary stenting in patients with atrial fibrillation (ENTRUST-AF PCI): a randomised, open-label, phase 3b trial. Issue 10206 (12th October 2019) - Vranckx, Pascal; Valgimigli, Marco; Eckardt, Lars; Tijssen, Jan; Lewalter, Thorsten; Gargiulo, Giuseppe; Batushkin, Valerii; Campo, Gianluca; Lysak, Zoreslava; Vakaliuk, Igor; Milewski, Krzysztof; Laeis, Petra; et al.
Summary: Background: We aimed to assess the safety of edoxaban in combination with P2Y12 inhibition in patients with atrial fibrillation who had percutaneous coronary intervention (PCI). Methods: ENTRUST-AF PCI was a randomised, multicentre, open-label, non-inferiority phase 3b trial with masked outcome evaluation, done at 186 sites in 18 countries. Patients had atrial fibrillation requiring oral anticoagulation, were aged at least 18 years, and had a successful PCI for stable coronary artery disease or acute coronary syndrome. Participants were randomly assigned (1:1) from 4 h to 5 days after PCI using concealed, stratified, and blocked web-based central randomisation to either edoxaban (60 mg once daily) plus a P2Y12 inhibitor for 12 months or a vitamin K antagonist (VKA) in combination with a P2Y12 inhibitor and aspirin (100 mg once daily, for 1–12 months). The edoxaban dose was reduced to 30 mg per day if one or more factors (creatinine clearance 15–50 mL/min, bodyweight ≤60 kg, or concomitant use of specified potent P-glycoprotein inhibitors) were present. The primary endpoint was a composite of major or clinically relevant non-major (CRNM) bleeding within 12 months. The primary analysis was done in the intention-to-treat population and safety was assessed in all patients who received at least one dose of their assigned study drug. This trial is registered with ClinicalTrials.gov, NCT02866175, is closed to new participants, and follow-up is completed. Findings: From Feb 24, 2017, through May 7, 2018, 1506 patients were enrolled and randomly assigned to the edoxaban regimen (n=751) or VKA regimen (n=755). Median time from PCI to randomisation was 45·1 h (IQR 22·2–76·2). Major or CRNM bleeding events occurred in 128 (17%) of 751 patients (annualised event rate 20·7%) with the edoxaban regimen and 152 (20%) of 755 patients (annualised event rate 25·6%) patients with the VKA regimen; hazard ratio 0·83 (95% CI 0·65–1·05; p=0·0010 for non-inferiority, margin hazard ratio 1·20; p=0·1154 for superiority). Interpretation: In patients with atrial fibrillation who had PCI, the edoxaban-based regimen was non-inferior for bleeding compared with the VKA-based regimen, without significant differences in ischaemic events. Funding: Daiichi Sankyo.